Kajian Upaya Pengendalian Penggunaan Tanah Di Kabupaten Temanggung Provinsi Jawa Tengah - Slamet Muryono (BHUMI: Jurnal Agraria dan Pertanahan, 2016)
ABSTRACT Limitations of the existence of natural resources, especially land, is increasingly felt both by the government as the manager of the land and the community as users of the land. Not only due to the increasing number of residents, but its speed of development is always in need of land to make the land users isincreasingly competitive. The object of the research is the use of land at the sites. LANDUSE is further correlated with the RTRW and LP2B for licensing the use of land in order to control the use of land. Instruments used in controlling the use of land consisting of Land Use Map (PT), Map of Spatial Plan (RTRW), and Sustainable Agricultural Land Map (LP2B). Conformity between the land use control instruments can be explained that the PT map with RTRW map, 77.58% rate of compliance in accordance with RTRW and 21.87% mismatch, while 0.55% of roads and rivers fit between PT and RTRW. Among LP2B map with PT map, 75.55% level of compliance in accordance with the LP2B direction, and mismatch much as 24.45%. Among RTRW map with LP2B map, compliance level is 89.45% in accordance with the LP2B direction, and 10.55% is not available.Keyword : Land Use, Spatial Planning, Sustainable Agricultural Land INTISARI: Keterbatasan keberadaan sumberdaya alam khususnya tanah, semakin hari semakin dirasakan baik oleh pemerintah sebagai pengelola tanah maupun masyarakat sebagai pengguna tanah. Hal ini karena luas tanah tetap tetapi yang menggunakan tanah, dari tahun ke tahun semakin meningkat. Masalah yang muncul adalah upaya untuk tetap menjaga keseimbangan lingkungan khususnya dalam kaitan dengan penggunaan tanah agar tetap sesuai dengan arahan dalam RTRW dan LP2B. Penelitian dilakukan di Kabupaten Temanggung.  Pendekatan spasial dilakukan dengan cara analisis tumpang susun (overlay) peta-peta. Objek penelitiannya adalah Peta Penggunaan Tanah (PT) di lokasi penelitian. Peta PT ini selanjutnya dikorelasikan dengan Peta Rencana Tata Ruang Wilayah (RTRW) dan Peta Lahan Pertanian Pangan Berkelanjutan (LP2B). Hasil penelitian menunjukan bahwa Instrumen yang digunakan dalam pengendalian penggunaan tanah terdiri dari Peta Penggunaan Tanah (PT), Peta (RTRW), dan (LP2B). Kesesuaian antar instrumen pengendalian penggunaan tanah tersebut dapat dijelaskan bahwa 78,13 % sesuai. antara RTRW dengan PT, dan 21,87 %  tidak sesuai. Antara LP2B dengan PT 75,55 % sesuai dan 24,45 % tidak sesuai. Antara RTRW dengan  LP2B 89,45 % sesuai dan 10,55 % tidak sesuai.